Association of Fcgamma receptor type 2A and 3A genotypes with rheumatoid arthritis in Chinese population. (February 2017) - Sun, Yining; Mo, Lingfei; Feng, Xiuyuan; Yang, Dongmei; Tan, Taochao; Zeng, Lingxia; Hui, Lingyun; Wang, Yawen; Liu, Cheng; He, Lan
Aim: SNPs of FcγRs were implicated in pathogenesis of rheumatoid arthritis (RA) and treatment efficacy of TNF inhibitors (TNFi). This study aims to investigate the associations of FcγRIIa and FcγRIIIa genotypes with autoantibody production and treatment response to TNFi in Chinese patients with RA.Patients & methods: FcγRIIa and FcγRIIIa polymorphisms were genotyped in 158 RA patients. Response to TNFi was evaluated in 18 patients at 3 and 6 months after treatment.Results: FcγRIIa-131H allele was significantly increased in autoantibody-negative RA patients. FcγRIIa-131H/H+H/R was closely associated with differences in 28-joint disease activity score in patients at months 3 and 6 of TNFi treatment.Conclusion: FcγRIIa-131H allele may have a protective role in autoantibody production and might be a biomarker for predicting good response to TNFi in Chinese RA patients.